Handbook of research on public information technology - Garson, G. David; Khosrowpour, Mehdi, 1951-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2008)
"This book compiles estimable research on the global trend toward the rapidly increasing use of information technology in the public sector, discussing such issues as e-government and e-commerce; project management and information technology evaluation; system design and data processing; security and protection; and privacy, access, and ethics of public information technology"--Provided by publisher.
Section 6. Selected Readings -- 67. Developing a Generic Framework for E-Government -- 68. A Web Query System for Heterogeneous Government Data -- 69. Digital Government Worldwide: An E-Government Assessment of Municipal Web Sites -- 70. User Help and Service Navigation Features in Government Web Sites -- 71. An Empirical Study on the Migration to OpenOffice.org in a Public Administration -- 72. Organisational Challenges of Implementing E-Business in the Public Services: The Case of Britain's National Mapping Agency -- 73. Public Administrators' Acceptance of the Practice of Digital Democracy: A Model Explaining the Utilization of Online Policy Forums in South Korea -- 74. E-Mexico: Collaborative Structures in Mexican Public Administration -- 75. The Impact of the Internet on Political Activism: Evidence from Europe -- 76. Adoption and Implementation of IT in Developing Nations: Experiences from Two Public Sector Enterprises in India.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Keywords: Internet in public administration; Blogging; Community informatics; Data mining in public administration; Design of e-government applications; Digital divide; Digital government; Digital libraries; E-census; E-commerce; E-government and SMEs; E-government innovation; E-government services; Electronic transactions in government; E-participation research; Ethical and policy issues; Government Web sites; Interactive personalized catalogues; Internet-based citizen participation; IT in emergency response; Legal issues in information technology; Local e-government; Public administration modernization; Public information and security; Public information technology; Public sector human resources information systems; Public sector participation in open communities; Public wireless internet; Social capital; Electronic books